Effect of chemical weed control and precision nitrogen management on yield and quality of late sown wheat (Triticum aestivum L.) - Sauhard Dubey; Mukesh Kumar; Vivek; Gaurav Shukla; Adesh Singh; P.K. Singh; U.P. Shahi (Annals of Agricultural Research, 2022)
The present study was carried out at the Crop Research Centre of Sardar Vallabhbhai Patel University of Agriculture & Technology, Meerut, (U.P.) during Rabi season of 2019-20 and 2020-21. The experiment was laid out in split plot design in which the precision nitrogen (N) management as main plot and chemical weed control as sub plot treatments with four replications. The precision N management treatments consisted of N1 - Absolute or Control, N2 - State recommendation (SR) @ 120:60:40, N3 - LCC Based N application, N4 - SPAD Based N application and four sub plot treatments (chemical weed control) W1 - Control (unweeded), W2 - Pinoxaden @ 40g a.i./ha + Metsulfuron methyl 5% (20g a.i./ha) applied at 30-35 DAS, W3 - Fenoxaprop-pethyl 10 WP (100 g a.i./ha) 30-35 days after sowing (DAS), W4 - Clodinafop 15 WP (100 g a.i./ha) 30-35 DAS. It was observed that chemical methods of weed control significantly reduced the weed density and dry weight of weeds effectively over control, hence increasing the yield of wheat peaking at 47.83 q/ha. The LCC based nitrogen application also gave significantly higher grain yield (46.97 q/ha) as compared to other treatments. The protein content (8.22%) and protein yield (393.64 kg/ha) was found to be maximum with application of Pinoxaden followed by Fenoxaprop whereas LCC based N application gave higher protein content (8.10%) and protein yield (381.34 kg/ha) as compared to SPAD based N application during both the years of experimentation.